Multichannel R-matrix analysis of 12C compound nucleus reactions - Alacayir, O.; Kam, E.; Yetkin, T.; Biyik, R.; Yalcin, T. (AMER PHYSICAL SOC, 2024)
We have calculated the cross sections (CS), differential cross sections (DCS), and astrophysical S factors for the reactions 11B(p, alpha 1) 8Be*, 11B(p, alpha 0) 8Be, 11B(p, p0) 11B, 11B(p, p1)11B*, 11B(p, gamma 0) 12C, 11B(p, gamma 1)12C*, and 11B(p, n0) 11C through a multichannel-multilevel R-matrix analysis. We have performed calculations for the energy range 100 keV-3.5 MeV and compared the calculated values with the experimental values. As a result, we have obtained the energy value, spin, and parity of some 12C excited levels within this energy interval. Additionally, we have determined the channel spins and angular momentum of the alpha 1 - 8Be*, alpha 0 - 8Be, p0 - 11B, p1 - 11B*, and n0- 11C pairs, as well as the electric and magnetic multipoles of the 11B(p, gamma 0) 12C and 11B(p, gamma 1)12C* channels. Although the analysis results and experimental data mostly agree, we have found some inconsistencies in the S-factor values for the 11B(p, p1)11B* channel at the 19.2-19.5 MeV energy interval. For the 11B(p, alpha 1) 8Be* decay channel of the 16.57 MeV (2-) resonance, the literature discusses which orbital angular momentum quantum value (l = 1 or l = 3) is true. We used both values in our analysis, and although no significant difference in the results were observed in the region of the 16.57 MeV (2-) resonance, we obtained a better fit with l = 3 values in the high energy region affected by the tail of this resonance.
Keywords: ENERGY CROSS-SECTIONS; FUSION-REACTOR; PROTON CAPTURE; NEUTRON YIELDS; LIGHT-NUCLEI; ALPHA; BORON; STATES; B-11(P,ALPHA)BE-8; RESONANCE; Physics